Photochemical Treatment of Drosophila APCs Can Eliminate Associated Viruses and Maintain the APC Function for Generating Antigen-Specific CTLs Ex Vivo - Ye, Jun; Yang, Chunxia; Cai, Zeling; Shi, Weixing; Yu, Hong (Mediators of Inflammation, 2018)
Drosophila cells transfected with MHC class I and a number of costimulation molecules including B7.1, ICAM, LFA-3, and CD70 are potent antigen-presenting cells (APCs) for the generation of antigen-specific cytotoxic T cells (CTLs) in vitro. Using Drosophila APCs, CTLs specific for melanoma antigens have been generated in vitro and adoptively transferred to melanoma patients. However, the recent discovery that Drosophila cells can carry insect viruses raises the potential risk of Drosophila APCs transmitting xenogenic viruses to patient CTLs. In this study, we have investigated photoreactive methods to inactivate insect viruses in APC. A clinical grade psoralen compound, 8-MOP (UVADEX) in combination with UVA treatment (5 joules/cm2) can be used to inactivate Drosophila cell viruses. UVADEX treatment is sufficient to inactivate insect viruses but does not affect the expression of MHC class I molecules and costimulation molecules on Drosophila APCs. In fact, UVADEX treatment prevents Drosophila APC growth while maintaining APC function. Furthermore, UVADEX-treated Drosophila APCs maintain or have enhanced APC function as determined by enhanced T cell activation, proliferation, and CTL generation. Thus, the use of UVADEX-treated Drosophila APCs may provide a valuable tool for immunotherapy to generate tumor antigen-specific CTLs.